LES-WASS-3D를 이용한 연안에서의 침수시뮬레이션 - 허동수(DONG-SOO HUR); 이우동(WOO-DONG LEE); 염경선(GYEONG-SEON YEOM) (Han-guk haeyang gonghak hoeji (Online), 2008)
The aim of this study is to investigate the inundation characteristics over coastal area due to the variation of sea level and plane arrangement of manholes using the 3D numerical model that is able to simulate directly interaction of WAve Structure Sandy beach(LES-WASS-3D). At first, The adopted model was validated through the comparison with an existing experimental data and showed fairly nice agreement. And then, the inundation characteristics over coastal area are discussed in relation to the variation of sea level and plane arrangement of manholes.